The Relationship of Coping Strategies, Self-Efficacy, and Scientific Attitudes towards Science Learning Outcomes of Fifth Grade Elementary School Students - Made Meilinda Dwi Lestari; I Gede Margunayasa; Diki (Jurnal Ilmiah Pendidikan Profesi Guru, 2023)
Lack of facilities and infrastructure limited teacher in utilizing science and technology and science become a factor causing learning loss. Strong and simultaneous collaboration between all educational personnel must be improved to realize the freedom of learning in Indonesian. The purpose of the study was to analyze the influence of coping strategies, self-efficacy, and scientific attitudes on science learning outcomes. The population in this study was 270 grade V elementary school student. The study sample totaled 159 students who were determined by proportional random sampling technique. Coping strategy data, self-efficacy data and scientific attitude data were collected with questionnaire sheets. Data on science learning outcomes are collected with an objective test in the form of a multiple choice test. Data were analyzed using SPSS 20 program-assisted multiple liner regression. The rcount value of coping strategies, self-efficacy, scientific attitudes and simultaneously greater than the rtable value. This shows that there is a significant positive influence between coping strategies on science learning outcomes. There is a significant positive influence between self-efficacy on science learning outcomes. There is a significant positive influence on scientific attitudes towards science learning outcomes. Simultaneously there is a significant positive influence of coping strategies, self-efficacy, and scientific attitudes on student science learning outcomes. Thus, it was concluded that there was a significant influence between coping strategies, self-efficacy and scientific attitudes on the results of science learning for fifth grade students of elementary school.